Livestock development in Nigeria: A survey of the policy issues and options - Williams, Timothy O. (International Livestock Centre for Africa, 1989)
The livestock subsector (LSS) has always been an important component of the Nigerian economy. Despite the importance of the sector, growth in livestock output has been slow. In the face of constraints posed by disease and ecological problems, government policies have not been totally successful in introducing or encouraging the development of basic technological and institutional changes necessary to exploit the potential that exists for an efficient growth of the LSS. The anatomy of these policies is the subject of this paper. It begins with a summary description of the LSS, including an analysis of trends in livestock distribution, production, trade and consumption. Throughout the paper attempts are made to examine the political economy of policy decisions in order to explain why certain policies are chosen when other alternatives appear to be available. A discussion of the lessons and suggestions for feasible policy changes in the futre concludes the paper.